1977
DOI: 10.1149/1.2133513
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Cell Studies on Ionic Carbide and Nitride Solutions in Molten Salts

Abstract: The free energy (Gibbs) of formation of Li2C2 , CaC2 , and Li3N and their activities in molten salt solutions at temperatures between 823° and 973°K have been determined by using the following galvanic cellsnormalFe,normalLi‐normalCa )(normalalloy|normalLiCl‐CaCl2 normaleut.CaC2|C)(normals,normalFe ][IandnormalFe,normalLi )(normalc|normalLiCl‐normalLiF eut.Li3N|N2 )(normalg,1 normalatm,normalFe ][IIThe nitrogen electrode used in cell (II) has been proved to have a Nernstian behavior by studying the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The electrolytic formation of nitrides from N 2 in molten alkali chlorides was reported prior to 1980. 337,338 Moreover, in 1998, Goto et al 339 reported that N 2 molecules can be electrochemically reduced to nitride ions (1/2N 2 + 3e − → N 3− ) in the molten eutectic mixture of LiCl−KCl (operating at 450 °C) at a nickel wire electrode. Since then, Murakami et al carried out a series of electrochemical ammonia synthesis experiments in the molten eutectic mixture of LiCl−KCl− CsCl containing 0.5 mol % Li 3 N, using hydrogen gas (H 2 ), 340,341 methane (CH 4 ), 342 hydrogen sulfide (H 2 S), 343 hydrogen chloride (HCl), 344 or water (H 2 O) 345,346 as the hydrogen source.…”
Section: N 2 Electroreduction In Molten Alkali Chloridesmentioning
confidence: 99%
“…The electrolytic formation of nitrides from N 2 in molten alkali chlorides was reported prior to 1980. 337,338 Moreover, in 1998, Goto et al 339 reported that N 2 molecules can be electrochemically reduced to nitride ions (1/2N 2 + 3e − → N 3− ) in the molten eutectic mixture of LiCl−KCl (operating at 450 °C) at a nickel wire electrode. Since then, Murakami et al carried out a series of electrochemical ammonia synthesis experiments in the molten eutectic mixture of LiCl−KCl− CsCl containing 0.5 mol % Li 3 N, using hydrogen gas (H 2 ), 340,341 methane (CH 4 ), 342 hydrogen sulfide (H 2 S), 343 hydrogen chloride (HCl), 344 or water (H 2 O) 345,346 as the hydrogen source.…”
Section: N 2 Electroreduction In Molten Alkali Chloridesmentioning
confidence: 99%
“…[7][8][9][10][11][12] In particular, it has been reported that molten LiCl, and related eutectics,p ossess the fascinating ability to stabilise the N 3À ion and establish the reversible N 2 /N 3À redox couple at ambient pressure. [13][14][15][16] Ito and co-workers proposed that this could be utilised in an ammonia synthesis process,by coupling the reduction of N 2 [Eq. (1)] at ac athode with its oxidation in the presence of H 2 [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the possibility of carbide‐based galvanic cells. Reported measurements of free energy and activity of ionic carbide allow a series of electrochemical applications for this molecule to be proposed. Electro‐oxidation of the acetylide ion in a molten LiCl–KCl–CaCl 2 –CaC 2 system leads to deposition of a carbon film on a copper substrate .…”
Section: Sustainable Access Usage and Recycling Of Calcium Carbidementioning
confidence: 99%